Cost Shifting in a Mental Health Carve-Out for the AFDC Population - Norton, Edward C. (CENTERS for MEDICARE & MEDICAID SERVICES, 1997)
This study tests whether the managed care vendor shifted costs to Medicaid-reimbursed medical care after the start of the mental health carve-out for the Aid to Families with Dependent Children (AFDC) population in Massachusetts. We used claims data over a 4-year period to estimate expenditures for four types of health services, two of which were paid for by the managed care vendor and two by Medicaid. Total per person public expenditures declined by only about 3 percent. Inpatient psychiatric services were replaced by outpatient psychiatric services and some pharmaceuticals, but overall there was little or no evidence of cost shifting to the medical sector. These results are in contrast to what was found in a sample of Medicaid beneficiaries eligible due to a mental health disability.